Social accessibility in queering code/space: Blued-based visibility and social practices of local gay people in mainland China - Xu, Tongwen; Zhang, Yansong (Frontiers in Psychology, 2024)
As a locative media, Blued articulates physical and digital space in the form of localization, giving a mediated visibility to its users who are not visible in physical space, thus making the city a queering code/space. This can transform social accessibility and the ways that gays come together and interact in local spaces. Taking mainland China, dominated by heteronomativity, as a field, this paper focuses on the visibility negotiation and social accessibility practices in Blued-based queering code/space. Using the digital anthropology method, this study found that Blued-based visibility is essential for non-closeted gay men to gain a sense of local belonging and community inclusion. Offline accessibility is a crucial demand for Blued users, but until then they have negotiated visibility through selective disclosure of social cues. At the same time, Blued users face visibility asymmetries and risks in the pursuit of accessibility. This study then argues that in the Blued-based queering code/space, the gay men constantly reconcile accessibility with others by managing visibility in a heteronormative urban space. In addition, this paper highlights the value of the hybrid of new media and physical space for the public interaction of marginalized groups in the city.